The Current Situation and Development of Chinese Language Education in Indonesian Universities in the New Era: A Case Study of the Department of Chinese Language, Universitas Sebelas Maret : 新时代印尼高校中文教育的现状与发展——以三一一大学中文系为例 - Phanata, Stephanie (Mandarinable: Journal of Chinese Studies, 2000)
Looking at the development of Chinese language education in Indonesia from the perspective of teaching Chinese as a foreign language, over the past few decades, considerable achievements have been achieved in the promotion of the Chinese language in Indonesia, with an increasing number of people learning Chinese language, even evolving the trend of the global Chinese language. This article explores the current situation and prospects of Chinese language education in Indonesian universities and the challenges and problems of Chinese language education in Indonesian universities. In promoting the development of Chinese language education, the academic community has gradually brewed some new ideas, hoping to encourage the globalization of Chinese language education through a brand-new structure, so that there will be further room for further development.